2007
DOI: 10.1007/s00005-007-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

The function of interleukin 17 in the pathogenesis of rheumatoid arthritis

Abstract: Interleukin (IL)-17 is a 30- to 35-kDa homodimeric polypeptide cytokine cloned in 1993 and originally named cytotoxic T lymphocyte-associated antigen-8 (CTLA-8). Sequencing the human genome resulted in the discovery of an additional five members of the IL-17 family that were consecutively named IL-17B to IL-17F. IL-17A is exclusively produced by a newly identified CD4+ T-helper subset that was recently named Th17. Differentiation of these cells from naive CD4+ T cells requires both TGF-beta and IL-6. IL-15 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 34 publications
1
47
0
2
Order By: Relevance
“…The autoimmune response in RA is initiated by the activation of antigen-specific T cells [15]. Th17 cells are a distinct subset of T helper cells that play a role in the activation of the immune system by stimulating pro-inflammatory cytokine production via IL-17 [16].…”
Section: Discussionmentioning
confidence: 99%
“…The autoimmune response in RA is initiated by the activation of antigen-specific T cells [15]. Th17 cells are a distinct subset of T helper cells that play a role in the activation of the immune system by stimulating pro-inflammatory cytokine production via IL-17 [16].…”
Section: Discussionmentioning
confidence: 99%
“…It acts on a variety of cells involving the development of autoimmunity, inflammation, and tumors. IL-17A and IL-17F genes share the highest degree of homology of about 50%, while the others have only 16%-30% of identity at the primary sequence level [126,[129][130][131][132] . IL-17F (OMIM 606496) is a novel proinflammatory cytokine which induces the expression of cytokines and chemokines.…”
Section: Il-17mentioning
confidence: 99%
“…The autoimmune response in RA is initiated by the activation of antigen-specific T cells. 15 Th17 cells are a distinct subset of T helper cells that play a role in the activation of the immune system by stimulating proinflammatory cytokine production via IL-17. 16 Results from studies using different arthritis models have demonstrated that IL-17-producing T-cells are the dominant cell type in the development of arthritis.…”
Section: Discussionmentioning
confidence: 99%